Measures of the therapeutic relationship in severe psychotic illness: a comparison of two scales. - Bale, R; Catty, J; Watt, H; Greenwood, N; Burns, T (2006)
BACKGROUND: A durable therapeutic relationship is central to mental health practice. The Working Alliance Inventory (WAI) and the Helping Alliance Questionnaire (HAQ) are established instruments for measuring such a relationship. AIMS: The project aimed to test the correlation between the two scales for patients with severe psychotic illness treated in an Assertive Community Treatment (ACT) team. METHODS: Ninety-one patients of an ACT team and their key-workers were recruited to complete the measures. RESULTS: Seventy-one patients (78%) completed the scales, and key-workers completed scales for every eligible patient. Both groups rated the relationship positively. There was a strong and significant correlation between the patient version of the WAI and the HAQ. There were significant but much weaker correlations between the patient-rated WAI and HAQ and the key-worker WAI. CONCLUSION: The patient version of the WAI and the HAQ seem to measure the patient's view of the relationship equivalently. The HAQ is simpler and easier to administer than the WAI.